1989
DOI: 10.1055/s-2007-1009296
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Islet Isolation, Cellular Composition and Secretory Response

Abstract: Porcine islets were isolated by infusion of a warm collagenase solution into whole pancreata followed by static incubation at 37 degrees C for 15 minutes. The pancreata were then chopped into small pieces and the free islets purified by filtration and centrifugation over a ficoll gradient. The insulin:amylase ratio of the islets compared to that in the intact pancreas was determined in 19 pancreata and indicates that the isolated islets were of a high degree of purity. The distribution of insulin, glucagon, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…We found that porcine islets with low basal percentage secretion rates (0-7 + 0-04%) still gave less than a twofold increase in insulin secretion in the presence of 16-7 mmol glucose/1 (1-3 + 0-13%). We have previously reported that por¬ cine islets lose a large proportion of their glucagon content during the isolation procedure (Crowther et al 1989). This hormone is thought to play an import¬ ant role in maintaining cyclic AMP within the cell at a level which allows the cell to respond fully to stimuli for insulin secretion (Schuit & Pipeleers, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that porcine islets with low basal percentage secretion rates (0-7 + 0-04%) still gave less than a twofold increase in insulin secretion in the presence of 16-7 mmol glucose/1 (1-3 + 0-13%). We have previously reported that por¬ cine islets lose a large proportion of their glucagon content during the isolation procedure (Crowther et al 1989). This hormone is thought to play an import¬ ant role in maintaining cyclic AMP within the cell at a level which allows the cell to respond fully to stimuli for insulin secretion (Schuit & Pipeleers, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Porcine islets were isolated using a modified version of the technique described by Crowther et al (1989). Briefly, warm collagenase was injected into the pancreas via the pancreatic duct.…”
Section: Porcine Islet Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sections were also ex¬ amined for insulin-like immunoreactive fluorescence us¬ ing guinea-pig anti-bovine insulin antibody (1:300 at 4°C overnight; raised at the University of Sussex by I C G) and fluorescein-conjugated anti-guinea-pig antibody from goat (1:16 at 37°C for 1 h). Non-specific binding was blocked by prior exposure of the sections to 10% goat serum for 10 min (Crowther et al 1989). …”
Section: Methodsmentioning
confidence: 99%
“…In contrast to foetal and neonate cells, islets from adult pigs are able to respond to hyperglycaemia within hours after transplantation [36][37][38][39]. Several studies, however, reported low insulin secretion from isolated adult pig islets [29,36,[40][41][42][43][44][45][46][47].…”
Section: Tools and Sources For Translation Into Clinical Practicementioning
confidence: 99%